“I Think of my Classroom as a Place of Healing”: Experiences of Indigenous Students in a Community-Based Master of Education Program in Saskatchewan - Oloo, James Alan; Relland, Michael (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation)

(untitled) (Department of Educational Administration, University of Saskatchewan, 2021)
An increase in the number of Indigenous teachers and education administrators is an important way to help improve Indigenous educational outcomes. However, while Indigenous teacher education programs in western Canada are registering increasing enrolments, master of education programs that prioritize Indigenous perspectives and pedagogies are rare in Canada. Using conversational method, this study examines experiences of six Indigenous students in a community-based master of education program that is a first of its kind in western Canada. The program is delivered by an Indigenous institution in partnership with a public university. The study is grounded in an Indigenous paradigm, namely, the Nehinuw (Cree) concepts of teaching and learning. Content analysis of data revealed five themes and sub-themes: (a) self-doubt; (b) a feeling of guilt as a result of family-work-school conflict; (c) self-advocacy; (d) re/connection with self, culture, and heritage; and (e) professional transformation. In general, a master of education degree is a requirement for educational administration positions including vice principal, principal, and superintendent. Understanding and acting upon the kinds of strategies that could enhance the success of Indigenous students in graduate programs is a key policy step in addressing the existing gaps in educational attainment between Indigenous and non-Indigenous Canadians.